Case of Nisin Oral Ingestion and its LC-MS/MS Detection in Human Urine Over Time: A Case Report - Kamarajan, Pachiyappan; Kassem, Ahmad; Radaic, Allan; Wohlschlegel, James; Kapila, Yvonne L (Archives of Clinical and Medical Case Reports, 2025)
Objective: Nisin is a bioactive peptide with antibacterial properties that has been examined for its therapeutic potential. This case report documents the development of a targeted mass spectrometry assay that accurately measures nisin levels in human urine following oral ingestion. Case presentation: Nisin ZP was orally ingested by a 59-year-old healthy white female then LC-MS/MS methodology was used to detect its excretion in human urine over time over 2 days. Briefly, 20 grams of nisin were ingested in two doses of 10 grams/150 ml of water. Sterile urine was then collected over 2 days. Urine was centrifuged to precipitate insoluble material followed by filtration through a 10 kilodalton molecular weight cutoff membrane. The filtrate was then concentrated by lyophilization, desalted, and then analyzed by LC-MS/MS. After online fractionation using C18 reversed-phase chromatography, the sample was electrosprayed into a Thermo Fusion Lumos mass spectrometer. Data was acquired using a parallel reaction monitoring (PRM) strategy focused on the +5 charge states of nisin. Extracted ion chromatograms for MS/MS fragments corresponding to those charge states were generated using the skyline algorithm and used for quantitation of nisin. Western blotting was also used to evaluate the presence of nisin in the urine samples. Results: Orally ingested nisin can be detected early in human urine after oral ingestion. Mass spectrometry data revealed that nisin was detected in urine samples 4-20 hours after the first ingestion and up to 14 hours after the second ingestion, indicating a potentially fast turnover and excretion of nisin in the human body. In line with the mass spectrometry data, immunoblotting data validated the findings, further supporting the notion of a fast turnover and excretion of nisin. Conclusion: We successfully applied the LC-MS/MS method to analyze nisin in urine obtained after oral administration of therapeutic doses of nisin. To the best of our knowledge, this constitutes the first report of nisin's detection following human oral ingestion and its presence in urine after excretion.